HAWA DIARIES: Mobile application for muslim women in Malaysia / Mohammad Musyrif Norasri - Norasri, Mohammad Musyrif (2019)
Nowadays the development of mobile application has been increased based on its popularity. The mobile application needed to be executed by using a smartphone to perform it. A mobile application was a program that design to run on any mobile device. The mobile application was not complete for people without a mobile device with them. In this era, the mobile device was needed for most people to do their daily routine. This research is focusing on the Hawa Diaries, an android mobile application for Muslim women in Malaysia to monitor their menstrual cycle. By using the information that has been posted in Jabatan Kemajuan Islam Malaysia's (JAKIM) official websites, this application will extract real-time prayer schedule from JAKIM Malaysia through e-solat application program interface (API). Although there is the application that already available on market and used by the users on prayer time and menstrual log, however, they need to install more than one application cater their needs. Furthermore, all these applications are not built specifically for Muslim women and do not have auto push notification for menstrual and prayer time. To solve this problem, by using java programming to write the hard code to link e-solat API with menstrual cycle log to get a functional application on guiding Muslim women in daily life. The working prototype of this project was developed by using Android Studio and SQLite database to store the data that extracted from e-solat API and stored menstrual log details information.